Ultrabright Red‐Emitting Photostable Perylene Bisimide Dyes: New Indicators for Ratiometric Sensing of High pH or Carbon Dioxide. Issue 42 (27th June 2018) - Pfeifer, David; Klimant, Ingo; Borisov, Sergey M.
Abstract: New pH‐sensitive perylene bisimide indicator dyes were synthesized and used for fabrication of optical sensors. The highly photostable dyes show absorption/emission bands in the red/near‐infrared (NIR) region of the electromagnetic spectrum, high molar absorption coefficients (up to 100 000 m −1 cm −1 ), and fluorescence quantum yields close to unity. The absorption and emission spectra show strong bathochromic shifts upon deprotonation of the imidazole nitrogen atom, which makes the dyes promising as ratiometric fluorescent indicators. Physical entrapment of the indicators into a polyurethane hydrogel enables pH determination at alkaline pH values. It is also shown that a plastic carbon dioxide solid‐state sensor can be manufactured by immobilization of the pH indicator in a hydrophilic polymer, along with a quaternary ammonium base. The influences of the plasticizer, different lipophilic bases, and humidity on the sensitivity of the sensor material are systematically investigated. The disubstituted perylene, particularly, features two deprotonation equilibria, enabling sensing over a very broad p CO2 range of 0.5 to 1000 hPa. Abstract : Seeing red : Highly photostable perylene dyes substituted in the bay position feature strong absorption and emission in the red/near‐IR part of the electromagnetic spectrum and are intrinsically pH sensitive. These ratiometric indicators are promising for measurements at high pH values and for application in optical carbon dioxide sensors.